INTERFACIAL INTERACTION IN CASTING ALUMINA MATRIX COMPOSITE ALLOYS BASED ON THE SYSTEM AL-SIO2 - A. V. Arabey (Литьë и металлургия)
The results of the analysis of the processes of interfacial interaction in casting alloys, based on the system Al- SiO2, obtained using heterophase (liquid-solid) mixing technology components-silica sand and aluminum are presented.